Penghambatan penyakit damping off (rebah semai) pada semai pinus dengan ekstrak biji nyiri (xylocarpus granatum) : (Inhibition of pine damping off disease by xylocarpus granatum extracts) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
ABSTRACT Forest Development in Indonesia is based on sustainable concept. To support this policy, forest protection must be done based on environmental approach. In this approach the use of synthetic pesticide must be minimized Consequently it is necessary to find out alternative method to substitute the use of synthetic pesticide. Phytofungicide is one of the alternative for the synthetic pesticide. The aim of the research was to evaluate the potential of tryiri (Xyloowus granatum Koen) seed as phytofungicide for controlling Fusarium sp., a pathogen of Pine damping off disease. Evaluation was done based on the activity of the extracted nyiri seeds collected from Cilacap mangrove in inhibiting the spore germination and germ tube length in the laboratory, and suppressing the disease intensity in green house. The results showed that the extract of nyiri had antifungal activity against the patogen tested This is the first report on the activity of nyiri as phytofungicide for plant pathogens. Key words: Xytocarpus granatum, Pine damping off disease, botanical fungicide. /NTISARI Penelitian ini bertujuan untuk mengetahui adanya bahan fungisida nabati dalam biji Nyiri (Xylocarpus granatum Koen) yang banyak twnbuh sebagai hutan payau. Biji yang dikumpulkan can hutan payau dt Cilacap dikeringkan, kemudian dibuat serbuk. Selanjutnya serbuk digunakan untuk membuat ekstrak dengan menggunakan pelarut etanol dan air. Potensi ekstrak yang diperoleh sebagai fungisida dievaluasi berdasarkan kemarnpuannya dalam mengfiambat Fusarium sp. (jarnur penyebab penyakit rebah semai pada semai Pinus) di laboratorium dan dt rurnah kaca. Hasil pengujian menunjukkan bahwa nyiri mengandung bahan yang mampu rnenghambat c pertumbuhan Fusarium sp. sehingga mempunyai peluang untuk dikembangkan sebagai fungisida nabati 'Warn rangka pengendalian penyakit tanaman hutan yang akrab linglamgan. Kata kunci: Xylocarpus granatum, penyakit semai pada pinus, fungisida nabati.